2015
DOI: 10.7883/yoken.jjid.2014.223
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Colistin-Associated Nephrotoxicity

Abstract: SUMMARY: Polymyxins have recently reemerged as a treatment option in response to the increasing number of resistant bacterial infections seen in recent years. Therefore, the current study aimed to determine the rate of and risk factors related to colistin-associated nephrotoxicity. All adult patients who had received colistimethate sodium (CMS) between 2010 and 2012 and met the inclusion criteria were included in the study. RIFLE (Risk, Injury, Failure, Loss of renal function and End stage of renal disease) cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
(10 reference statements)
2
23
1
4
Order By: Relevance
“…Temocin et al reported a similarly low NT rate (48%); however, they did not specify the disease severity scores or comorbidities of patients, which may contribute to NT (23).…”
Section: Discussionmentioning
confidence: 97%
“…Temocin et al reported a similarly low NT rate (48%); however, they did not specify the disease severity scores or comorbidities of patients, which may contribute to NT (23).…”
Section: Discussionmentioning
confidence: 97%
“…Undoubtedly, nephrotoxicity is the most clinically relevant and dose‐limiting adverse reaction of the polymyxins. The incidence of nephrotoxicity varies widely in the literature from 0% to more than 60% largely due to heterogeneous patient populations, differing definitions of nephrotoxicity, wide ranges of polymyxin doses administered, and differences in both severity of illness and the presence/absence of various other risk factors for the patients being studied . Contemporary studies, using commonly accepted polymyxin doses and AKI definitions, place the rate of associated nephrotoxicity in the 20–50% range for both polymyxins …”
Section: Clinical Questions and Recommendationsmentioning
confidence: 99%
“…When P. aeruginosa is resistant to all other treatment options, which has been occurring with increasing frequency, clinicians may opt to use polymyxins due to a lack of alternative options, despite their high rate of associated nephrotoxicity. Nephrotoxicity rates of 30–50% are seen with both colistin and polymyxin B . Other limitations of the polymyxins include the lack of a well‐defined optimal dosing regimen for colistin and a lack of clinical experience with polymyxin B .…”
Section: Treatment Regimens For Resistant Gram‐negative Infectionsmentioning
confidence: 99%
“…Nephrotoxicity rates of 30-50% are seen with both colistin and polymyxin B. 50,51 Other limitations of the polymyxins include the lack of a well-defined optimal dosing regimen for colistin and a lack of clinical experience with polymyxin B. 12 A comprehensive review of the polymyxins is beyond the scope of this manuscript but may be found elsewhere.…”
Section: Treatment Regimens For Resistant Gram-negative Infectionsmentioning
confidence: 99%